A New Adaptive Control for Five-Phase Fault-Tolerant Flux-Switching Permanent Magnet Motor - Hongyu Tang; Wenxiang Zhao; Chenyu Gu (International Journal of Rotating Machinery)
The five-phase fault-tolerant flux-switching permanent magnet (FT-FSPM) motor can offer high efficiency and high fault-tolerant capability. In this paper, its operation principle is presented briefly and its mathematical model is derived. Further, a new adaptive control for an FT-FSPM motor, based on the backstepping method and the sliding mode control strategy, is proposed. According to the backstepping method, the current controllers and voltage control laws are designed to track the speed and minimize the current static error, which enhance the dynamic response and the ability to suppress external disturbances. In order to overcome the influence of parameter variations, according to sliding mode control theory, the virtual control variables and the adaptive algorithm are utilized to approach uncertainty terms. Three Lyapunov functions are designed, and the stability of the closed-loop system is analyzed in detail. Finally, both simulation and experimental results are presented to verify the proposed control method.